2014
DOI: 10.1016/j.crohns.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Once versus three times daily dosing of oral budesonide for active Crohn's disease: A double-blind, double-dummy, randomised trial

Abstract: Budesonide at the recommended dose of 9 mg/day can be administered OD without impaired efficacy and safety compared to 3mg TID dosing in mild-to-moderately active Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The recommended daily dose is 9 mg orally for up 8 weeks . The full effect is usually achieved within 2–4 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended daily dose is 9 mg orally for up 8 weeks . The full effect is usually achieved within 2–4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The recommended daily dose is 9 mg orally for up 8 weeks. 18 The full effect is usually achieved within 2-4 weeks. For maintenance of clinical remission, the dosage of 6 mg daily is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…For induction of remission, an oral dose of 9 mg/day is recommended, given as 9 mg once‐daily or 3 mg t.i.d., to be continued for up to 8 weeks. Once‐daily dosing appears to be as effective as 3 mg t.i.d . and may support improved adherence.…”
Section: Oral Budesonide In Crohn's Diseasementioning
confidence: 96%
“…Numerous randomized trials have compared budesonide versus placebo or comparator therapies, and assessed different dosing regimens, for the induction of remission in Crohn's disease. Meta‐analyses based on these trials have shown that oral budesonide is more efficacious than mesalazine or placebo when used for the induction of remission in mild to moderate active Crohn's disease, with no difference in side effects .…”
Section: Oral Budesonide In Crohn's Diseasementioning
confidence: 99%
“…In trials utilizing the CDEIS, a score < 6 [67] has been used to define partial endoscopic healing or endoscopic remission and <3 [67], 4 [68], ≤4 [69] or 0 [70] to define complete mucosal healing. In trials utilizing the SES-CD a score of <3 [69,71,72,73] or equal to 0 [24,70,[74][75][76] has previously been used to define endoscopic remission or minimal endoscopic activity although a study by Moskovitz et al [77] validated the cutoff values as 0-2 for endoscopic remission, 3-6 for mild endoscopic disease, 7-15 for moderate endoscopic disease activity and ≥16 for severe endoscopic disease activity. In regard to defining endoscopic response to treatment, Ferrante et al [78] demonstrated that a decrease from baseline of both the CDEIS and the SES-CD score of at least 50 % was most predictive of corticosteroid free remission by week 50.…”
Section: Endoscopic Disease Activity Assessment In Crohn's Diseasementioning
confidence: 99%